Do Ultraconservative Access Cavities Hinder Endodontic Reintervention in Mandibular Incisors? A Laboratory Investigation - Caroline Meurer Luiz; Taynara Santos Goulart; Ketillyn da Silva Magalhães; Gilmar da Rosa Souza Junior; Lucas da Fonseca Roberti Garcia; Josiane de Almeida (Hindawi Limited, 2024)
This study assessed the influence of the type of endodontic access cavity on endodontic reintervention. Twenty mandibular central incisors were distributed into two groups (n = 10): TradAC group-traditional access cavities and UltraAC.Inc group-ultraconservative access cavities. After endodontic access, the root canals were prepared and obturated by the single cone technique. The filling material was removed with the Reciproc R25 instrument, followed by reinstrumentation with the R40 instrument. Images acquisition of each root canal hemisection was performed in a stereomicroscope to quantify the amount of remaining filling material. The amount of remaining filling material attached to the root canal walls was expressed in square millimeter (mm2). Data were statistically analyzed (one-way ANOVA and post hoc Student's t-tests). There was no statistically significant difference between TradAC and UltraAC.Inc groups (p>0.05). None of the tested endodontics' access showed root canal walls completely free of filling material. Ultraconservative access cavities in mandibular incisors had no negative impact on the filling material removal.